Pengaruh Pemanfaatan Media Sosial Dalam Pembelajaran Digital Marketing Terhadap Peningkatan Pengetahuan Ibu Pembina Kesejahteraan Keluarga (PKK) - Tri Ginanjar Laksana; Ariel Maulana Wibowo; Imam Aji Pranoto; Nadjib Kurnia Budiawan; Alfian Dwi Nugroho; Pagi Muhamad; Azka Fauzan Firaus; Muhammad Rofi Ariansyah; Ahmad Nada Kusnendar; Nuri Annisa; Enny Istanti; Julyanto Ekantoro; Nur Maulana; Ulis Nansa Anwar; Devina Arimbi Dwimita Putri; Fatur Yanuardi Leksono; Aditya Maulana Syahputra; Ailsa Agripina; Ginaris Putri Ilhami; Silvi Nur Baitti; Sintia Rahayu; Dwi Aulya Yunitasari; Alfajri Ramadhan; Hindun Nurun Ala; Maulana Akbar Fadhillah; Iwan Abadi (Jurnal Kajian Ilmiah, 2023)
The aim of this research is to determine the effect of using social media in digital marketing learning on increasing knowledge of community pedagogical competence, especially PKK women, regarding information technology in Sekarwangi Village, Cibadak District, Sukabumi Regency. This research was conducted at the house of the citronella oil refinery in Sekarwangi Village, Cibadak District, Sukami Regency. The population of this study was 40 PKK women, with a sample size of 19 people, in determining the sample using the Slovin formula with an error tolerance of 5%. This research method approach is quantitative research with a correlation analysis design. The instruments used consist of the use of social media, digital marketing and pedagogical knowledge. The data collection technique uses an instrument in the form of a questionnaire and is analyzed using descriptive and inferential statistical analysis. The research results show that there is a very significant positive influence between the variable use of social media for digital marketing learning on pedagogical competence with a low strength of relationship (r = 0,584 p<0.01). The existence of a positive relationship means that the higher the use of social media for digital marketing learning, the higher the pedagogical competence related to information technology. The theories used in this research are not yet extensive, it would be good in the future that scientific developments will enable the emergence of new theories that can explain the increase in pedagogical knowledge in the field of information technology, which can then provide different results in other research.